Traditionality and modernity in Romani non-folklore literature: The stereotypical motivic analysis contrasted to the structural one - Červenka, Jan (Romano džaniben, 2019)
The article follows the opposition of traditionality and modernity in the literatureof the so-called Slovak Roma. The author explores texts which refer to theancient past of the Roma (mythic proses by Margita Reiznerová, some fairy talesby Elena Lacková) as modern individual texts that construct Romani identityin a non-traditional mode. Similarly, he regards selected texts with motives fromthe past but relatively recent life in Romani settlements (poetry by Vlado Oláh,proses by Erika Olahová) as individual fiction with hardly any folklore influence.On the other hand, he points out texts fully representing folklore despite using verymodern motives. Based on this contrast the author warns against the dominanceof motivic analysis in the classification of Romani literature and he also shows oneimportant complementary line of modern Romani literature.
Keywords: development; folklore; modern literature; Roma; Romani literature